Prevalence of metabolic syndrome and the comparison of fasting plasma glucose and HbA1c as the glycemic criterion for MetS definition in non-diabetic population in Ghana - Annani-Akollor, Max Efui (Diabetol Metab Syndr, 2019)
BACKGROUND: Glycated hemoglobin (HbA1c), owing to its ability to reflect glycemia over a relatively longer time span, is still been investigated as an adjunct test for fasting plasma glucose (FPG) to identify subjects at risk of metabolic syndrome (MetS) in some Caucasian populations. However, whether or not HbA1c can serve as an adjunct to FPG in the definition of MetS in the Ghanaian population remains unknown. This study determined the prevalence of MetS and evaluated HbA1c ≥ 5.6% and FPG ≥ 5.6 mmol/l as the glycemic component of MetS among non-diabetic population in Ghana. METHODS: This was a case–control study conducted at St Francis Xavier Hospital, Assin Fosu, Central Region, Ghana. A total of 264 non-diabetic Ghanaian adults consisting of 158 newly diagnosed hypertensives and 106 normotensives, were recruited for the study. Fasting plasma insulin and glucose, HbA1c, and lipid profile was performed for each respondent. RESULTS: Using the FPG as glycemic criterion, the overall MetS prevalence was 46.6%, 37.1%, and 12.5% according by the IDF, NCEP ATP III, and WHO criteria, respectively. The prevalence of MetS using the HbA1c criterion was 54.2%, 52.7%, and 42.4% by the IDF, NCEP ATP III and WHO criteria, respectively. The HbA1c criterion identified more participants with MetS compared to the FPG criterion with a good agreement between HbA1c and FPG using the IDF and NCEP ATP III criteria (κ = 0.484 to 0.899) respectively. However, the overlap between HbA1c and FPG based diagnosis of MetS was limited for the WHO criterion. CONCLUSION: The prevalence of metabolic syndrome is high among non-diabetics in Ghana. Introduction of HbA1c in addition to FPG in the screening of MetS improves identification of more people with MetS who would otherwise have been missed when only FPG-based diagnosis of MetS is used; with a substantial agreement with FPG, except when using the WHO criteria. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13098-019-0423-0) contains supplementary material, which is available to authorized users.